Keilmuan Hukum Islam dalam Perspektif Epistemologis - Idri, Idri (Program Pascasarjana UIN Sunan Ampel Surabaya, 2008)
This paper is aimed at exploring the epistemological aspect of the science of Islamic Law, that is, its methods and procedures of analysis. For this purpose, the paper makes use of the deductive-coherency method, inductive-correspondence method, scientific method, phenolmenological method, and functional as well structural method. The paper argues that procedures in studying Islamic Law consists of there levels of analysis, namely taxonomy analysis, competence analysis and information processing. In reading Islamic Law in this way, it is hoped that this science may be developed along side with other social sciences and humanities.